Homo scribens в образному світі драматургії Лесі Українки - Кочерга, Світлана; Kocherha, Svitlana (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті досліджується архетип gomo scribens та поетика скрипторики на матеріалі творів Лесі Українки («Кассандра», «Руфін і Прісцілла», «Камінний господар», «Адвокат Мартіан») у межах художньої антропології. The research claims the expediency to explore the artistic phenomenon "homo scribens" within anthropology science. The object of the study is intertextual scryptor layer of Lesia Ukrainka's texts. The theoretical basis of the research is the studies of Barthes, Derrida, Epstein. There are the main connotation of the notion "scriptor" in the article. The art works of Lesya Ukrainka contain the extensive system of characters which we can call scriptors. They represent elite segments of society. The writer actualize the motif of broken communication and focuses on the appearence of a script as creation of meaning. This article provides an overview of the historical specificity of the act of writing that is fixed in Lesya Ukrainka's dramas (Antiquity, the Roman era, the Middle Ages). There are different kinds of scripts that play an important role in the drama story (letter, treatise, legal document, grave inscription, draft, etc). The analysis of the motivation of writing focuses on the scriptor characters in dramas "Rufin and Priscilla", "Stone Master", "Advocate Martian". It is proved that Lesya Ukrainka tried to raise the intellectual level of the Ukrainian literature by adressing to the homo scribens theme. She managed to enrich the plot constructions and helped to expand the interpretive potential of the text.
Homo Scribens in the Figurative World of Lesya Ukrainka's Dramas
Keywords: скрипторика; антропологія; scriptor; anthropology